Anaerobic degradation of palm oil mill effluent (POME) at 60 days of hydraulic retention time (HRT) in an anaerobic bench scale reactor (ABSR) - Yee, Shian Wong; Ong, Soon An; Nabilah, Lutpi; Fahmi, Muhammad Ridwan (Universiti Malaysia Perlis (UniMAP), 2011)
Malaysian International Conference on Trends in Bioprocess Engineering (MICOTriBE) 2009 organized by School of Bioprocess Engineering, Universiti Malaysia Perlis in collaboration with Ministry of Higher Education & Inno Biologics Sdn Bhd, 12th - 13th December 2009 at Dewan Tun Dr. Ismail A, Putra World Trade Center (PWTC), Kuala Lumpur, Malaysia.